Non-dimensional analysis of depth, orientation, and alignment in acoustic power transfer systems. (13th November 2018) - Christensen, David B; Roundy, Shad
Abstract: Acoustic power transfer systems are typically comprised of an electrical source, acoustic transmitter (TX), medium through which the acoustic waves propagate, acoustic receiver (RX) and an electrical load. The voltage generated across and power delivered to the load from the TX is a function of RX position (depth, orientation, and alignment relative to the TX), frequency, TX and RX diameter, and source and load impedance. In applications where the RX position is not fixed, such as in implantable medical devices, slight disturbances in RX position can result in a severe reduction in load voltage and power. Therefore, the sensitivity of voltage and power as a function of RX position is crucial to system design. This paper presents an analysis of the load voltage and power as a function of RX depth, orientation, alignment, frequency, RX and TX diameter, and load impedance. Design graphs are developed and presented as a means of visualizing the sensitivity of voltage and power to system parameters. Non-dimensional design graphs are then generated to broaden the applicability of simulation results.